Do Sesamia nonagrioides (Lepidoptera; Noctuidae) Gravid Females Discriminate Between Bt or Multivitamin Corn Varieties? Role of Olfactory and Visual Cues. Issue 1 (5th April 2015) - Cruz, Diego; Eizaguirre, Matilde
Abstract : The Mediterranean corn borer, Sesamia nonagrioides Lefèbvre, is a key pest of corn and a main target of Bacillus thuringiensis (Bt) corn in Northeast Spain . Trends for future biotechnology crops indicate that Bt, non-Bt, and stacked corn varieties with metabolic pathways for vitamin-increased traits could coexist in same region. Knowledge of the oviposition response of gravid females of S. nonagrioides to these different varieties could be extremely important for managing strategies aimed for delaying resistance development. In dual-choice assays, we examined the host preference of gravid females of S. nonagrioides for four corn varieties: a new transgenic corn with increased vitamin levels, its near isogenic counterpart (M37W), a Bt corn plant, and its near isogenic counterpart. Olfactory cues were the predominant ones when gravid females looked for a suitable host to lay eggs, and no synergistic effects were observed when both visual and olfactory cues were present. When the plant was visible, the females preferred the odors emitted by the nontransgenic to its multivitamin transgenic counterpart and when they only could detect the volatiles they also preferred the nontransgenic M37W variety to the Bt corn variety. If gravid females are less attracted to corn with an increased level of vitamins, this could impact insect resistance management and the value of refuge plants, if such traits are stacked with an insect resistance trait.